Peculiarities of cultural news coverage in Swedish national newspapers - Tolstonogova, Irina V. (Journal of the Belarusian State University. Journalism, 2023)
Using the study of two leading Swedish national newspapers «Dagens Nyheter» and «Svenska Dagbladet», the author makes an attempt to generalise some peculiarities of cultural news coverage. The article presents the main stages of the formation of cultural journalism in the analysed newspapers, highlights the most popular genres and topics of cultural publications, and also describes a unique hybrid approach to cultural news coverage.
Keywords: cultural journalism; Sweden; «Dagens Nyheter»; «Svenska Dagbladet»; print media